2019
DOI: 10.1021/acssuschemeng.9b04661
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Small Molecular Hydrocarbons over ZnO Nanostructures: The Difference between Methane and Ethylene and the Impact of Polar and Nonpolar Facets

Abstract: The development of efficient photocatalysts to oxidize small molecular hydrocarbons under atmospheric conditions is of great significance. In our previous study, it was found that nanosized ZnO can fulfill this purpose with unprecedented activity. However, the difference between the hydrocarbons and the impact of polar and nonpolar facets of ZnO are far from understood. Herein, by the successful synthesis of facet-dependent ZnO photocatalysts with predominantly (0001)- and (011̅0)-facets-exposed single-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 58 publications
(115 reference statements)
1
27
0
1
Order By: Relevance
“…Similarly, Yi and co‐workers demonstrated that methane molecules preferred to bind to the single‐electron‐trapped surface defects (i.e., OVs) on polar facets of ZnO, leading to activation of methane under light irradiation. [ 114 ] Apart from ZnO, Wang and co‐workers reported the TiO 2 with Ti 3+ species for highly selective photocatalytic oxidation of CH 4 into CO with the assistance of external bias. [ 105 ] As investigated by in situ Raman spectroscopy and in operando attenuated total reflection Fourier‐transform infrared spectroscopy (ATR‐FTIR), they found that the presence of Ti 3+ benefited to the formation of a Ti 3+ —C bond, further resulting in selective production of CO while the absence of Ti 3+ favored the formation of a Ti 4+ —O—C bond, easily lead to the complete oxidation of CH 4 into carbonates (Figure 16b).…”
Section: Applications Of Defects In Photocatalytic Methane Conversionmentioning
confidence: 99%
“…Similarly, Yi and co‐workers demonstrated that methane molecules preferred to bind to the single‐electron‐trapped surface defects (i.e., OVs) on polar facets of ZnO, leading to activation of methane under light irradiation. [ 114 ] Apart from ZnO, Wang and co‐workers reported the TiO 2 with Ti 3+ species for highly selective photocatalytic oxidation of CH 4 into CO with the assistance of external bias. [ 105 ] As investigated by in situ Raman spectroscopy and in operando attenuated total reflection Fourier‐transform infrared spectroscopy (ATR‐FTIR), they found that the presence of Ti 3+ benefited to the formation of a Ti 3+ —C bond, further resulting in selective production of CO while the absence of Ti 3+ favored the formation of a Ti 4+ —O—C bond, easily lead to the complete oxidation of CH 4 into carbonates (Figure 16b).…”
Section: Applications Of Defects In Photocatalytic Methane Conversionmentioning
confidence: 99%
“…[22][23][24][25][26][27] In addition, morphology control and surface modification are also able to alter the range of light absorption. [28][29][30][31] 2) Effective separation of the photogenerated electrons and holes.W hen as emiconductor is irradiated by light, the photoexcited electron transfers from the valence band (VB) to the conduction band (CB), thereby leaving ahole in the VB.T he electron-hole pairs are generated in femtoseconds,but aconsiderable number of electron-hole pairs recombine spontaneously.T he surviving electrons and holes are able to move to the trapping sites within picoseconds to nanoseconds,o rt ransfer to the adsorbed reactant molecules within microseconds to milliseconds. [32][33][34] Additionally,t he electrons and holes will also recombine in the trapping sites or in the bulk during the transfer process.T he recombined charge carriers release energy as light or heat without participation in the redox reaction.…”
Section: Absorption Unitsmentioning
confidence: 99%
“…Oxygen is anonmetallic oxidant with ahigh reactivity and low toxicity that possesses the ability to readily form various oxides with most elements and compounds.Oxygen is widely used as the oxidant in av ariety of oxidation reactions, including the photooxidation of methane. [20,21,26,30,31,36,55,[101][102][103][104] Themain reactions of the methane-oxygen system are TOM and POM. TOM offers the possibility of efficiently removing trace amounts of methane,while POM offers an eco-friendly way to produce syngas,C 2 hydrocarbons,a nd oxygenates at RT and ambient pressure.…”
Section: Methane-oxygen Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 94 ] Recently, the complete photocatalytic oxidation of methane has attracted increasing attention. [ 78,95–103 ] The Yi group reported that Ag‐modified ZnO (Ag/ZnO) nanostructures showed very high photocatalytic activity for CH 4 oxidation under simulated‐sunlight illumination. [ 78 ] It was found that the built‐in electric field of a ZnO polar semiconductor promotes the separation of photogenerated electrons and holes.…”
Section: Photocatalytic Conversion Of Methanementioning
confidence: 99%